2007
DOI: 10.1128/jvi.02167-06
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Antigen Presentation after Acute Vesicular Stomatitis Virus Infection

Abstract: Long-term antigen expression is believed to play an important role in modulation of T-cell responses to chronic virus infections. However, recent studies suggest that immune responses may occur late after apparently acute infections. We have now analyzed the CD8 T-cell response to vesicular stomatitis virus (VSV), which is thought to cause to an infection characterized by rapid virus clearance by innate and adaptive immune system components. Unexpectedly, virus-encoded antigen was detectable more than 6 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
89
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 56 publications
2
89
0
Order By: Relevance
“…A critical question for measles is the causal relationship between persistence of MeV RNA and the induction of prolonged immune suppression and lifelong immunity. Considering that low levels of viral antigen are important for continued stimulation of CD8 + T cells after acute infections with influenza and vesicular stomatitis viruses (44,45), and that MeV RNA persists in the blood and lymphoid tissue for more than 2 mo after infection, we speculate that lifelong protective immunity after primary MeV infection could be a consequence of prolonged antigen stimulation. Because we predict that recrudescence of infectious MeV might occur in individuals with impaired humoral immune responses, another key area for future work is to assess implications for measles transmission and persistence at the population level.…”
Section: Resultsmentioning
confidence: 99%
“…A critical question for measles is the causal relationship between persistence of MeV RNA and the induction of prolonged immune suppression and lifelong immunity. Considering that low levels of viral antigen are important for continued stimulation of CD8 + T cells after acute infections with influenza and vesicular stomatitis viruses (44,45), and that MeV RNA persists in the blood and lymphoid tissue for more than 2 mo after infection, we speculate that lifelong protective immunity after primary MeV infection could be a consequence of prolonged antigen stimulation. Because we predict that recrudescence of infectious MeV might occur in individuals with impaired humoral immune responses, another key area for future work is to assess implications for measles transmission and persistence at the population level.…”
Section: Resultsmentioning
confidence: 99%
“…Early experiments indicated that pMHCI complexes survive in only the very short term after infectious influenza A virus clearance (6,22), leading to the conclusion that the maintenance of influenza-specific CD8 ϩ T cell memory is antigen independent. Recent findings have suggested that influenza pMHCI complexes may persist for 1 month or more after the active infection is controlled (8,9,11,23). If this is indeed the case, it is incumbent on us to reinterpret the nature of influenza A virusspecific CD8 ϩ T cell memory.…”
Section: Discussionmentioning
confidence: 99%
“…ns, P Ͼ 0.05; *, P Յ 0.05; **, P Յ 0.01; ***, P Յ 0.001 (by paired, two-tailed Student's t test). (51)(52)(53). Thus, we cannot rule out the possibility that residual lytic antigen or reactivation-associated antigen that is not suppressed by cidofovir treatment in vivo continuously interferes with restoration of CD8 ϩ T cell effector capabilities during MHV68 infection in IFNAR1 Ϫ/Ϫ mice.…”
Section: Ifnar1mentioning
confidence: 99%